1992
DOI: 10.1007/bf00180286
|View full text |Cite
|
Sign up to set email alerts
|

Elevated lipoprotein(a) levels in patients with acute myeloblastic leukaemia decrease after successful chemotherapeutic treatment

Abstract: Twenty-two patients with acute myeloblastic leukaemia (AML) were studied to investigate disease-associated changes in lipid metabolism. Lipoprotein (a) [Lp(a)] levels were found to be elevated at the time of diagnosis (median 23 mg/dl; 41% of patient group had levels greater than 25 mg/dl) and diminished after successful chemotherapeutic treatment in 9 of 10 cases, with a maximum decrease from 56 to 10 mg/dl. In contrast, reduced levels of total cholesterol, low density lipoprotein (LDL) and high density lipop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
(11 reference statements)
1
5
0
Order By: Relevance
“…It has been reported that the serum Lp(a) level was high in subjects with leukemia, and after remission the level decrease [26]. In our present study, the serum Lp(a) level did not change after total prostatectomy in subjects without estrogen.…”
Section: Statistical Analysis Serum Lp(a)supporting
confidence: 49%
“…It has been reported that the serum Lp(a) level was high in subjects with leukemia, and after remission the level decrease [26]. In our present study, the serum Lp(a) level did not change after total prostatectomy in subjects without estrogen.…”
Section: Statistical Analysis Serum Lp(a)supporting
confidence: 49%
“…[6], the Lp(a) levels were enhanced initially, but after about 2 weeks of treatment Lp(a) levels started to decrease gradually to the original levels. It is well‐known that APL patients are metabolically unstable, which amongst other things is noticeable in the fluctuation of Lp(a) values [6], and elevated serum Lp(a) levels have been reported in leukaemia [14]. It cannot therefore be excluded that the disease did influence the effects of retinoids on lipoproteins and that the increase in Lp(a) is secondary to other changes.…”
Section: Effect Of Treatment With Placebo or Isotretinoin On Concentrmentioning
confidence: 99%
“…Plasma Lp(a) levels are typically elevated under conditions of physiologic stress, such as extended long-distance running (Cardoso et aI. 1994), pregnancy (Desoye et al 1987), and thoracic surgery (Maeda et al 1989), as well as in specific disease states such as cancer (Wright et al 1989, Niendorf et al 1992, Kokoglu et al 1994) and renal disease (Dieplinger et al 1993, Buggy et al 1993). This lipoprotein may play an important role in tissue synthesis and repair.…”
mentioning
confidence: 99%